Cultivo de surubim pintado (Pseudoplatystoma corruscans) e híbrido (P. reticulatum X P. corruscans) em sistema de recirculação de água - Miranda, Mário Olindo Tallarico de (2012)
This study aimed to test a pilot recirculating aquaculture system (RAS) and to evaluate in this system the effects of the stocking density on the production of species of surubim pintado , Pseudoplatystoma corruscans, and its hybrid with P. reticulatum regarding the effect of stocking density and water renewal rate on the hybrid production. The study lasted for 84 days. The physical and chemical conditions in the RAS was evaluated by measuring water consumption (223,6 L/kg of fish produced), temperature (25,8±0,7ºC), dissolved oxygen (5,33±0,04 mg/L O2 in the water inlet to culture tanks), pH (6,75±0,25), total alkalinity (40,0±20,6 mg/L CaCO3), carbon dioxide (16,6±6,1 mg/L CO2), total suspended solids (8,0±4,2 mg/L TSS), total ammonia nitrogen (0,18±0,10 mg/L NH3-N), nitrite (0,163±0,090 mg/L NO2-) and nitrate (58,0±9,7 mg/L NO3-). To evaluate the fish performance, two experiments were conducted simultaneously. In experiment 1, densities of 40, 80 and 120 fish.m-3 (approximately 8.5, 17 and 25.5 kg.m-3) for the pure and the hybrid lineages were tested using a 3 x 2 factorial design (three densities and two lineages). In experiment 2, only the hybrid lineage was used, and three stocking densities were tested: 20, 40 and 60 fish.m-3 (approximately 9, 18 and 27 kg.m-3) and two water renewal rates (1 L/kg.min-1 and 0,5 L/kg.min-1), using a 3 x 2 factorial design (three densities and two water renewal rates). Fish were fed with extruded food (40% crude protein) at a rate of 2.5% of the body weight per day. For both experiments, daily specific growth rate (SGR), final weight, biomass gain, final density, food conversion, final weight and dissolved oxygen levels at the tank outlet are discussed. In experiment 1, both lineages showed to be adapted to the RAS, but the hybrid lineage had a better performance than the pure lineage. In experiment 2, the highest water renewal rate resulted in a better performance, and an increase in density improved the final production.